Rehabilitation of the historic center of the city of M’sila, a situation to be taken care of - Kara, Abdelhamid; Benkhaled, Elhadj (Technium Social Sciences Journal, 2022)
Algerian cities, like other cities, the Mediterranean in particular, have not been spared the negative influence of certain factors such as weather, nature, and people (combined or sporadic) that have been imposed on them. Imposed, which has lost some of its momentum, their function and their sense of civilization. However, the old and historic urban fabric of these cities has experienced most of the impact. As in most Algerian urban centers, the city center of M’sila is part of the old residential districts which are experiencing a number of problems that have affected its urban and functional status, and which reflect the way of life of its inhabitants, which has led to the appearance of urban disorder and the dissemination of a distorted urban image of the architectural heritage of this region. Over time, he became unable to keep pace with developments and was far from his aspirations. In order to know the mechanisms necessary to rehabilitate its urban sphere and work to develop it and preserve this cultural heritage, and to contain this phenomenon, we had to seek to reform this situation with the aim of providing conditions of comfort to its inhabitants. In this study, we have therefore opted for the search for the most important causes which are at the origin of the problems encountered by the center of this city, and consequently to propose appropriate solutions to this situation, while preserving the ancient heritage of the city, which would correspond to its characteristics and ingredients and work for its development and promotion.